P629 Evolution of disease phenotype, time to biological therapy and medium-, long-term surgery rates in Crohn's disease patients in Western Hungary – a population-based study between 2007–2018, data from the Veszprem county cohort. (21st January 2022) - Gonczi, L; Lakatos, L; Golovics, P; Pandur, T; David, G; Erdelyi, Z; Szita, I; Lakatos, P L
Abstract: Background: The number of prospective population-based studies evaluating the natural disease course and surgical outcomes of Crohn's disease(CD) are still limited from Eastern Europe. The present study is a continuation of the Veszprem IBD population-based cohort with a follow-up of the incidence and disease course of IBD since 1977. Our aim was to evaluate disease course by examining progression in disease phenotype, time to biological therapy and surgery rates in a prospective population-based database from Veszprem Province, including incident CD patients diagnosed between January1, 2007 and December31, 2018. Methods: Data of 421 incident CD patients were analyzed(male/female:237/184; median age at diagnosis:29 years(y)[IQR: 21–42]). Both in-hospital and outpatient records were collected and comprehensively reviewed at diagnosis and during clinical follow-up. The mean length of follow-up was 8.53y(SD: 3.3). Probability of medium-, long-term change in disease course and surgical outcomes were analyzed. Results: Disease location was ileal(L1), colonic(L2) in and ileo-colonic(L3) in 29.7%/24.5%/45.8% of patients at diagnosis. At the end of follow-up(8.53y), disease location was 27.1%/22.8%/50.1%(L1/L2/L3). The proportion of patients with upper gastrointestinal manifestation remained stable(7.6% and 8.1%), while perianal disease increased from 13.5% to 19% by the end of follow-up. Disease behavior at diagnosis was luminal(B1) in 62.5% of the patients. The probability of disease behavior progression from luminal into stenosing or penetrating phenotype was 11.9%(SE:1.7) at 3 years, 13.2%(SE:1.7) at 5 years and 17.6%(SE:1.7) at 10 years. Figure 1. The Probability of receiving biological therapy after diagnosis was 20.9%(SE:2.0) at 5 years and 28.8%(SE:2.0) at 10 years in this cohort. Overall resective surgery rate was 29.5% in the total population, while perianal surgery rate was 31.3% in patients with perianal disease at the end of follow-up. The probability of resective surgery was 20.7%(SE:2.0) at 1 year, 26.1%(SE:2.2) at 5 years and 30.7%(SE:2.4) at 10 years. Figure 2. For the probability of first perianal surgery among patients with perianal disease see Figure 3 . Conclusion: The probability of progression in disease behavior was lower compared to data from previous decades and similar to results from recent pan-European population-based data. (Burisch 2018, JCC). One-year surgery rates after diagnosis were considerably higher compared to previous data from our cohort or compared to Western and Northern European centers. (Lakatos 2011, IBD ). Medium-term(5y) surgery rates were similar( 20%) compared to recent Hungarian and European data, while long-term(10y) rates decreased compared to data from previous decades. (Lakatos 2011, IBD; Lakatos 2012, AJG).